2017
DOI: 10.1590/0074-02760170182
|View full text |Cite
|
Sign up to set email alerts
|

Dengue serotype-specific immune response in Aedes aegypti and Aedes albopictus

Abstract: BACKGROUNDDengue viruses (DENV) are considered one of the most important emerging pathogens and dengue disease is a global health threat. The geographic expansion of dengue viruses has led to co-circulation of all four dengue serotypes making it imperative that new DENV control strategies be devised.OBJECTIVESHere we characterize dengue serotype-specific innate immune responses in Aedes aegypti and Aedes albopictus using DENV from Puerto Rico (PR).METHODS Ae. aegypti and Ae. albopictus were infected with dengu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
(68 reference statements)
0
28
0
Order By: Relevance
“…The disconnect between kinetics in intermediate tissues and those of the salivary glands suggests that there are either stochastic processes driving kinetics in early tissues that do not predict how many viruses make it to the salivary glands, or that factors affecting replication rate in the salivary glands are somewhat independent [23]. For example, previous research has demonstrated that the strength and efficacy of immunity varies across tissues [23] and in response to different serotypes [41]. It is also possible that DENV is modulating the vector immune response in a strain- or tissue-dependent manner [42].…”
Section: Discussionmentioning
confidence: 99%
“…The disconnect between kinetics in intermediate tissues and those of the salivary glands suggests that there are either stochastic processes driving kinetics in early tissues that do not predict how many viruses make it to the salivary glands, or that factors affecting replication rate in the salivary glands are somewhat independent [23]. For example, previous research has demonstrated that the strength and efficacy of immunity varies across tissues [23] and in response to different serotypes [41]. It is also possible that DENV is modulating the vector immune response in a strain- or tissue-dependent manner [42].…”
Section: Discussionmentioning
confidence: 99%
“…The related gene expression level was normalized to the expression of the Ae. aegypti ribosomal protein S7 gene (GenBank Accession # AY380336) [ 45 ]. The levels of gene expression were compared to non-infectious blood-fed mosquitoes.…”
Section: Methodsmentioning
confidence: 99%
“…The factor which leads to the drastic increase in the prevalence of the disease is rapid urbanization with poor water and drainage management. 4 Urban poverty in India tops 25 percent; about 81 million people stay below the poverty line in metropolitan areas. In India, the urban poor are counted out by rural ones.…”
Section: Introductionmentioning
confidence: 99%